Evaluation of Denpasar Type C Terminal Facilities to Improve Quality and Efficiency - Yudi Martha Wiguna, I Wayan; Hidoyoa, Muhamad Siraj Arkhandaffa; Ahmad, Rahmat; Dwipayana, Arif Devi (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2024)
In 2016, Ubung Denpasar Terminal transitioned from Type A to Type C, as determined by the Mayor of Denpasar through Decree Number 188.45/1060/HK/2016. Located on Jalan Cokroaminoto, Ubung Village, North Denpasar District, Denpasar City, this terminal serves as a vital transportation hub. However, due to infrastructure problems and damage, all Inter- Provincial Buses ceased operations at Ubung Terminal. Consequently, the terminal now exclusively serves mini/micro buses within the province and Trans Metro Dewata in Bali Province. To address the terminal’s needs, comprehensive research was initiated to evaluate facility shortages through inventory analysis. Using a qualitative descriptive analysis methodology, the research aims to identify improvement areas, aligning with the technical guidelines in the Decree of the Directorate General of Land Transportation Number 271/ HK.105/DRJD/96 concerning technical specifications for public passenger vehicle stops. The expected outcomes are to enhance the functionality, safety, and comfort of Ubung Terminal, thereby increasing the efficiency and effectiveness of public transportation services in Denpasar